Reducing Intervention in the COVID-19 Era: Opportunities for Vital Pulp Treatment - El karim, Ikhlas A.; Duncan, Henry F. (Frontiers in Dental Medicine, 2021)
Over the last 12 months, the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2) virus has emerged as a significant global health problem with extensive repercussions for the practice of dentistry. As the principle transmission-route is via droplet-spread, aerosol-generating dental procedures (AGPs) present an exquisite challenge, which either has to be avoided or performed using strict infection-control measures, which increase the deployment of resources and cost. This new working environment necessitates the adoption of simplified, yet effective procedures that reduce intervention and minimise clinical chair time to short, single visits. Vital pulp treatment (VPT) has emerged as an attractive, technically less-complicated group of biologically-based management strategies that are aimed at maintaining pulp vitality and avoiding root canal treatment (RCT). These procedures are carried out in a strict aseptic environment using a rubber dam and have a reported high success rate, suggesting that they could be considered as effective and simple alternative therapies to relieve pain and avoid multiple visit RCT and other endodontic procedures. The relevance of promoting a simple, predictable and effective alternative to traditional, more complex dentistry has never been more compelling. In this perspective article, the latest advances in VPT are highlighted, along with an analysis of their relative success and compelling reasons why we as dentists should be adopting these treatment approaches. Thereafter, the indications, case selection, prognostic factors, techniques, limitations and future prospects of these procedures are discussed.